Mixed sugarcane and elephant grass silages with or without bacterial inoculant - Cavali, Jucilene; Pereira, Odilon Gomes; Valadares Filho, Sebastião de Campos; Porto, Marlos Oliveira; Fernandes, Francisco Eden Paiva; Garcia, Rasmo (Revista Brasileira de Zootecnia, 2009)
The effects of different ratios of sugarcane and elephant grass (0:100, 25:75, 50:50, 75:25 and 100:0% of the natural basis) were assessed on the chemical composition and losses in silages treated with a bacterial inoculant, using laboratory silos. A 2 × 5 factorial arrangement (with and without inoculant and five elephant grass ratios) in a randomized blocks design with three replications was used. Interaction was observed in the sugarcane and elephant grass ratio × bacterial inoculant for crude protein (CP) and pH. The other variables were influenced only by the increasing proportions of elephant grass. The contents of dry matter, neutral detergent fiber corrected for ashes and protein, acid detergent fiber, insoluble protein in acid detergent fiber, hemicellulose and lignin in the silages increased linearly with the proportions of elephant grass. The water soluble carbohydrate contents and dry matter in vitro digestibility of the silages decreased linearly with the increase in the proportion of elephant grass. The mean value of ammonia nitrogen in relation to total N was 7.0% (% of DM). The CP values of the inoculated and non-inoculated silage fitted linear models. The highest CP content was observed in the silage treated with inoculant. The pH values of the silages, with and without inoculant, fitted quadratic and linear models, respectively. The lactic acid, propionic acid and butyric acid contents were not influenced by the elephant grass ratios, while the acetic acid content, for the non-inoculated silages, and ethanol decreased linearly with the increase in elephant grass. The ratio of 25% sugarcane and 75% elephant grass improves the nutritional value and increases the silage DM recovery, because of the lower effluent and gas productions. The homofermentative bacterial inoculant does not affect the sugarcane silage.

Avaliou-se o efeito de diferentes relações de cana-de-açúcar e capim-elefante (0:100; 25:75; 50:50; 75:25 e 100:0% na matéria natural) sobre a composição química e as perdas em silagens tratadas com inoculante bacteriano utilizando-se silos laboratoriais. Adotou-se um esquema fatorial 2 × 5 (com e sem inoculante e cinco proporções de capim-elefante), em delineamento inteiramente casualizado, com três repetições. Observou-se interação relação cana e capim-elefante × inoculante para a composição em proteína bruta (PB) e o pH. As demais variáveis foram influenciadas apenas pelas relações crescentes de capim-elefante. Os teores de MS, fibra em detergente neutro corrigida para cinzas e proteína, fibra em detergente ácido, proteína insolúvel em detergente ácido, hemicelulose e lignina nas silagens aumentaram linearmente com as proporções de capim-elefante. Por sua vez, o teor de carboidratos solúveis e a digestibilidade in vitro da MS das silagens decresceu linearmente com o aumento da proporção de capim-elefante. O valor médio do nitrogênio amoniacal foi de 7,0% na MS. Os valores de PB das silagens inoculadas e não-inoculadas ajustaram-se a modelos lineares, crescentes e decrescentes, respectivamente. Observou-se maior teor de PB nas silagens tratadas com inoculante. Os valores de pH das silagens, com e sem inoculante, ajustaram-se a modelos quadráticos e lineares, respectivamente. Os teores de ácido lático, propiônico e butírico não foram influenciados pelas proporções de capim-elefante, enquanto os teores de ácido acético, no caso das silagens não-inoculadas, e de etanol decresceram linearmente com o aumento do nível de capim-elefante. A relação de 25% de cana-de-açúcar e 75% de capim-elefante melhora o valor nutricional e aumenta a recuperação da MS ensilada, em decorrência das mais baixas produções de efluentes e gases. O inoculante bacteriano homofermentativo não tem efeito na silagem de cana-de-açúcar.
Keywords: Effluent; Ethanol; Nutritional value; Organic acids; Soluble sugars